An Investigation into the Effects of Asperities on Geomembrane/Geotextile Interface Shear Characteristics - Adeleke,Daniel (Department of Civil Engineering, 2022)
Geomembranes are often utilized as fluid barriers in geotechnical applications such as landfills. Due to their relative impermeability and chemical resistance characteristics, they are usually used alongside other geosynthetics like geotextiles in landfills to constitute base, side-slope, and cover liner systems. Uniquely, within the side-slope liner composite system, which consists of multiple geosynthetics interfaces, the geomembrane/geotextile (GMB/GTX) interface is known to have relatively low shear strength. In an effort to mitigate sliding failure occurrence at the GMB/GTX interface, asperities have been incorporated into GMB manufacturing to increase the shear characteristics. Presently, many GMB with various asperities properties is now available because of asperities proven advantage. Challengingly, only a few studies have substantiated and quantified the importance of varying asperities properties (height, density, and shape) on the GMB/GTX interface. Therefore, this study was aimed at investigating the effects of asperities variation on GMB/GTX interface shear characteristics and mechanism, as well as to identify the asperity parameters combination which optimizes the GMB/GTX interface shear strength. The GMB/GTX interface shear tests were conducted according to ASTM D5321, under saturated conditions with the “305 mm by 305 mm” direct shear box at applied normal stresses; 25 kPa to 400 kPa. In this research, the two common geotextile polymers (polypropylene and polyester) in South Africa were used at the GMB/GTX interface. Also, the geomembranes used had their asperity height varied from 0 mm to 2.02 mm, while the asperity density and shape were varied from 0 to 663 spikes per 10000 mm2 , and conical to hook-cone asperity shape, respectively. GMB/GTX interface shear results showed that with a 70 % increase in the geomembrane asperity height at constant asperity density, friction angle increased by 25 %. Also, an average increase of 25 % in the friction angle was observed as asperity density was doubled at constant asperity height. However, the friction angle was not significantly affected by changes in asperity shape from conical to “hook-cone” shape. Therefore, among identified asperities and roughness features, asperity height together with surface roughness affect the GMB/GTX interface shear parameter more dominantly. These outcomes present a better explanation of the “fibre/asperity” interaction at the GMB/GTX interface and identified asperity properties which optimised surface interaction. The optimised interaction produces efficient shear mechanism that would ultimately lead to a stable and durable landfill liner system.